Analisis Faktor Risiko Fraud terhadap Manajemen Laba pada Perusahaan Food and Beverage yang Terdaftar Di Bei Periode 2020–2024 - Friska Andani; Sudrajat Sudrajat (AKUNTANSI 45, 2026)
Earnings management driven by fraudulent financial reporting motives can distort financial information and reduce stakeholder trust in capital market stability. This study aims to examine the effect of Fraud Pentagon risk determinants, namely pressure, opportunity, rationalization, competence, and arrogance, on earnings management in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. This sector was selected due to its vulnerability to financial manipulation amid intense competition and economic fluctuations. This quantitative study uses secondary data obtained from annual reports and applies purposive sampling, resulting in a sample of 25 companies with 68 panel data observations. Earnings management was measured using discretionary accruals based on the Modified Jones Model, while hypothesis testing employed multiple linear regression analysis. Firm size was included as a control variable. The results indicate that opportunity, represented by the proportion of independent commissioners, and firm size have a positive and significant effect on earnings management. These findings suggest that the presence of independent commissioners may not always ensure effective monitoring, while larger firms tend to exploit the complexity of business transactions. In contrast, pressure, rationalization, and competence show no significant effect, while the arrogance variable could not be tested due to the consistent implementation of the two-tier board system. The findings highlight the importance of strengthening corporate governance mechanisms to reduce opportunities for opportunistic earnings manipulation.